Feasibility Test of Articulate Storyline 3 Learning Media Based on Local Wisdom for Optimizing Students’ Algebraic Thinking Skills - Wian Azrillia; Rina Oktaviyanthi; Khotimah Khotimah; Mark Lester B. Garcia (PAEDAGOGIA, 2024)
This research focuses on assessing the suitability of learning media developed using Articulate Storyline 3. The foundation of local wisdom is integrated into the media to enhance algebraic thinking skills among students. The study analyzes the learning media's design, content, and effectiveness, emphasizing its potential to optimize algebraic thinking. The research employs a comprehensive evaluation, incorporating expert validation, small-scale testing, and field trials. Thirty-seven students were involved as research participants, with seven individuals for the pilot and 30 for the field scale tests. Meanwhile, five experts were employed to validate the designed instructional media. The instrument used to assess the feasibility of the instructional media was a questionnaire consisting of 32 items for student responses and 36 items for expert validators, with 17 points allocated to media experts and 19 to mathematics experts. The results demonstrate a high feasibility rating of 93,38%, indicating the efficacy of the Articulate Storyline 3-based learning media. Furthermore, students responded positively to the media, with an overall interest rating of 88,39%. The research also reveals a moderate increase in algebraic thinking skills, as reflected in the average n-gain index of 0,46 for small-scale testing and 0,39 for field-scale testing. The recommendations for future research include considerations for using free hosting to ease accessibility, enhancing interactivity in the presentation of teaching materials, and expanding the learning media to encompass diverse subjects aligned with students' needs. This study contributes valuable insights into developing and assessing technology-based learning tools, emphasizing their potential to optimize algebraic thinking skills among students.